PENGARUH KUALITAS PELAYANAN, HARGA, DAN CITRA PERUSAHAAN TERHADAP LOYALITAS DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA GOJEK MALANG (Studi Pada Mahasiswa Jurusan Manajemen Fakultas Ekonomi Universitas Islam Malang) - Fadhil Fadhlur R; N Rachma; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to determine and analyze the influence of Service Quality, Price, Company Image on Satisfaction of Gojek Malang Customers. Knowing and analyzing the effect of Consumer Satisfaction on Consumer Loyalty of Gojek Malang. Knowing and analyzing the influence of Service Quality, Price, Company Image on Consumer Loyalty of Gojek Malang. Knowing and analyzing the influence of Service Quality, Price, Company Image on Consumer Loyalty through Satisfaction of Gojek Malang Customers. The population of this study were Gojek users in FEB UNISMA 2018 in the amount of 238, while the sample was 70 customers. Data analysis using Path analysis.The results of the study show that Service Quality has a direct effect on loyalty. While the price and corporate image do not affect consumer loyalty. Satisfaction directly affects Consumer Loyalty. satisfaction is able to mediate the relationship of the influence of service quality on loyalty, but satisfaction is not able to mediate the influence of price and corporate image on consumer loyalty.Keywords: Service Quality, Price, and Corporate Image, Loyalty, Satisfaction